2016
DOI: 10.1111/ijcp.12822
|View full text |Cite
|
Sign up to set email alerts
|

Health benefits of multicomponent training programmes in seniors: a systematic review

Abstract: Overall, this review demonstrates a positive effect of MCT with functional benefits and positive health outcomes for seniors. Based on this evidence, clinicians should encourage all adults aged 65 or over to engage in MCT programmes to favour healthy ageing and keeping older members of our society autonomous and independent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
113
0
24

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(161 citation statements)
references
References 67 publications
(298 reference statements)
11
113
0
24
Order By: Relevance
“…Indeed, this trial has shown a beneficial effect on mental health and well‐being although the rates of clinically significant depression and anxiety were very low. This is also consistent with previous reports from which the benefits of AT on mental health and well‐being were reported . In a review conducted by Gogulla et al, the authors concluded that AT was the most effective type of training to improve depressive symptoms in seniors.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Indeed, this trial has shown a beneficial effect on mental health and well‐being although the rates of clinically significant depression and anxiety were very low. This is also consistent with previous reports from which the benefits of AT on mental health and well‐being were reported . In a review conducted by Gogulla et al, the authors concluded that AT was the most effective type of training to improve depressive symptoms in seniors.…”
Section: Discussionsupporting
confidence: 90%
“…In order to counter this trend towards sedentary and disability, the current literature supports the benefits of regular physical activity . As a result, exercise training (and more particularly aerobic training—AT) is now one of the key components of the general lifestyle strategy to maintaining/improving physical, functional and mental health all along the life course according to the WHO (World Health Organization), including in senior and older people .…”
Section: Introductionmentioning
confidence: 99%
“…Higher levels of cardiorespiratory fitness, lower extremity strength, balance and reaction time were found to be associated with better gait in several populations, such as community dwelling older adults (Ploutz-Snyder et al 2002;Tiedemann et al 2005;Callisaya et al 2010), patients with multiple sclerosis (Sandroff et al 2013) and stroke survivors (Eng & Tang 2007;Taylor-Piliae et al 2012). Physical exercise has also been found effective to improve gait and walking capacity in multiple populations, such as older adults (Gill et al 2004;Eggenberger et al 2015;Bouaziz et al 2016), stroke survivors (Saunders et al 2016) and people with dementia (Bossers et al 2015;Kemoun et al 2010). Because low physical fitness levels have been demonstrated in people with ID (Lahtinen et al 2007;Hilgenkamp et al 2010), this may also influence their gait.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to the American College of Sports Medicine exercise guidelines of 2-3 times per week for older adults (Nelson et al, 2007), and a recent review exploring effective exercise training in the older population (Bouaziz et al, 2016), our participants attended the exercise intervention group only once a week. Literature about exercise dose for people with…”
Section: Discussionmentioning
confidence: 88%